The sedimentology and palaeoenvironmental significance of vlei sediments on the Winterberg range, South Africa - Dewey, Felicity Joy (Rhodes University, Faculty of Science, Department of Geography, 1989)
Palaeoenvironmental reconstruction of the late Pleistocene and Holocene geological periods for central and southern Africa has been hampered by the erratic distribution of suitable sites, incomplete and inaccurately dated sequences and the limited nature of published data. One geomorphological feature which has supplied valuable evidence for fluctuations in past environmental conditions, is the vlei or dambo. The type-site of these waterlogged features is in south central Africa, but similar features have been described on other continents. The clastic and organic sediments contained within these features are affected by, and therefore reflect to some degree, the environment under which they were formed. The characteristics of the sediments supply information as to their transport and mechanisms of deposition. From these processes, the environmental conditions at the time of vlei formation can be inferred. The environmental history of the Eastern Cape region has been considerably neglected, and is far less well understood than other countries such as Malawi, Zambia and Zimbabwe. A study site in the Winterberg Range (Eastern Cape) was selected which permitted the comparison of two vleis, the objective being to establish an accurate late Pleistocene sediment chronology for the entire plateau area. Radiocarbon dates from organic layers indicate that these sediments span the last 12 000 years BP, suggesting that organic accumulation at this site began at roughly the same time as at sites further afield. The vlei sediments are analysed in terms of their morphology, particle slze distribution, and other physical and chemical characteristics. These data facilitate the construction of detailed stratigraphic diagrams and a chronological summary of sediment accumulation, from which the period and governing processes of vlei development under changing environments may be described. It is found that the Winterberg vleis contain sediments which respond to changes in the prevailing environment. This makes these sediments useful indices from which to trace such changes during the late Pleistocene and Holocene times. These features are found to be similar in many respects to those described elsewhere in Southern Africa. The study attempts to provide greater understanding of contemporary vlei processes and emphasises the necessity of their preservation, as finite and valuable resources, by future generations
Keywords: Geology, Stratigraphic -- Holocene; Sedimentology; Sediments (Geology) -- South Africa -- Eastern Cape -- Winterberg range; Geology, Stratigraphic -- Pleistocene; Paleoecology -- South Africa -- Eastern Cape -- Winterberg range